2011
DOI: 10.1111/j.1464-410x.2010.09910.x
|View full text |Cite
|
Sign up to set email alerts
|

Heparin prophylaxis and the risk of venous thromboembolism after robotic‐assisted laparoscopic prostatectomy

Abstract: Study Type – Therapy (case series)Level of Evidence 4What’s known on the subject? and What does the study add?The incidence of deep venous thrombosis (DVT) in major urological surgery has decreased over time with the introduction of pharmacological prophylaxis, early mobilization, and the use of sequential mechanical compression devices. We examined the value of heparin prophylaxis in robotic assisted laparoscopic prostatectomy (RALP), where the risk of DVT is already low.The rate of thromboemolic events withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The results seem to support the conclusion from the registration trials with hip and knee surgery that dabigatran is also both effective and safe after prostate cancer surgery. In keeping with the earlier reports suggesting that VTE is rare after minimally invasive prostate cancer surgery [2,3], only one clinically evident VTE was detected in this cohort, translating to an incidence of only 0.25%. The observed low VTE risk could suggest that the prophylactic policy was even too extensive.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results seem to support the conclusion from the registration trials with hip and knee surgery that dabigatran is also both effective and safe after prostate cancer surgery. In keeping with the earlier reports suggesting that VTE is rare after minimally invasive prostate cancer surgery [2,3], only one clinically evident VTE was detected in this cohort, translating to an incidence of only 0.25%. The observed low VTE risk could suggest that the prophylactic policy was even too extensive.…”
Section: Discussionsupporting
confidence: 92%
“…A VTE rate of only 0.5% was reported after laparoscopic prostatectomy or robotic assisted laparoscopic prostatectomy (RALP) in a large multiinstitutional retrospective analysis of almost 6000 patients across the USA and Europe [2]. A recent single-institution comparative cohort analysis found a low VTE rate that was not affected by the use of heparin [3]. Thus, some authors have suggested that thromboprophylaxis using heparin may not be justified after minimally invasive prostate cancer surgery [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,15,18 Although only 1% of patients in our series required transfusions, we observed that blood transfusion and not simply blood loss appeared to increase the risk of VTEs. This observation is similar to observations in studies of other cancer types that have noted this relationship and found increased risk per unit transfused, suggesting a mechanism from the transfusion itself.…”
Section: Discussionmentioning
confidence: 53%
“…In both groups the incidence of symptomatic VTE was comparable (1.0% vs. 0.7%) [221]. The other authors also report relatively low incidence of symptomatic VTE (0.5-0.6%) in laparoscopic or robotic prostatectomy [220,222]. On the other hand, some reports suggest higher risk for such complications despite of antithrombotic prophylaxis administration in this clinical settings.…”
Section: Venous Thromboembolism Prophylaxis In Cancer Patientsmentioning
confidence: 81%